Analysis of investment opportunities available to small businesses and investment clubs in Gauteng Province - Tanzi, Yongama (My University, 2020)
This study investigated the factors driving investments and investment behavior by Small Medium and Micro Enterprises (SMME) and Investment clubs in Gauteng, South Africa. The study is a qualitative study, using in-depth interviews and focus group discussions with business owners and club members. Thematic analysis was used to analyse the qualitative data collected. The findings reveal that there is high awareness of available investment opportunities by SMME’s and Investment clubs, but low rates of investment activity driven by fear, entrepreneurial behaviours, lack of financial literacy, coupled with a lack of trust in the economy and the banking system. The results also show that the property sector is the most preferred and well-known investment opportunity to most SMMEs. The need to encourage the development of better financial knowledge amongst black SMME and Investment club owners/members was also highlighted. It is recommended that the Department of Trade and Industry (DTI) provide affordable investment training for SMMEs and registered investment club members. This will help them broaden their knowledge of recent and current investment philosophy.
A dissertation submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Small Medium and Micro Enterprises (SMME); SMME; Investment; Gauteng; SDG-8: Decent work and economic growth